Adoption Behaviour of Climate-resilient Agricultural Practices in Punjab under NICRA Project - Sodhi, G. P. S.; Singh, R. K.; Dhillon, G. S.; Ahuja, Sanjeev; Kaur, Arvindpreet; Sunidhi,; Kaur, Taranreet; Murai, Ashish S.; Singh, Rajbir; Kaur, Simerjeet (Indian Journal of Extension Education, 2023)
An integrated package of climate-resilient technologies was demonstrated in one village per 4 selected districts namely Bathinda, Faridkot, Roopnagar and Fatehgarh Sahib of Punjab. The major objective was to augment the resilience of agricultural systems, both crop production and livestock farming to climate vulnerability. From 2011-2020, major interventions made in crop production system were; crop residue management, zero tillage, quality seed, green manuring, biofertilizers and promotion of water saving technologies such as laser land levelling, direct seeded rice, short to medium duration rice varieties, etc. Major interventions made in livestock production system included green fodder production round the year, silage making, mineral mixture, uromin lick availability and regular vaccinations. To improve livelihood, subsidiary occupations like dairy farm, backyard poultry, piggery, jaggery production and protected cultivation units were established in the NICRA villages. Farmers were highly convinced to adopt the recommended practices but adoption level of demonstrated natural resource management technologies was variable and specific to a district. The satisfying results were witnessed under the NICRA project and there was an increase in the adaptive capacities, and enhanced incomes. NICRA villages functioned as model villages and became knowledge hubs/centres for out-scaling technologies in large areas.
Keywords: Climate change; Resilience; Impact; Adoption; Technologies; NICRA